An IoT-based system for collision detection on guardrails - Gomes, Tiago Manuel Ribeiro (2016)
Wireless Sensor Networks (WSNs) have been employed in a wide range of applications due to the low-cost and ease of installation features. One of the applications is in the road safety and highways, in a wide range of scenarios. In this paper, an IoT-based system for collision detection on guardrails is presented. The developed system implements an IoT standard stack in order to provide the connectivity and interoperability of the network devices. Also a theoretical analysis for the energy consumption is presented and simulated. A Markov Chain model is used to observe the energy consumption of the proposed algorithm in each node. An experimental evaluation is also carried out in order to check the theoretical analysis and it was based on the real energy consumption of the developed nodes. At last, a full deployment on a highway of the developed system allowed a full evaluation of the connectivity and performance of the whole system.